Bisphenol A and polychlorinated biphenyls enhance the cancer stem cell properties of human ovarian cancer cells by activating the WNT signaling pathway. (May 2020) - Guo, Yifan; Li, Bin; Yan, Xu; Shen, Xinming; Ma, Juan; Liu, Sijin; Zhang, Daoqiang
Abstract: Cancer stem cells (CSCs) are a very small subpopulation that have stem-cell qualities, such as exhibiting self-renewal, immortality, and pluripotency, and the capability to differentiate into different tumor cell subtypes. CSCs contribute to tumor onset, expansion, metastasis, resistance and recurrence. Meanwhile, organic pollutants, including nonpersistent pollutants, such as bisphenol A (BPA), and persistent pollutants, such as polychlorinated biphenyls (PCBs), are toxic chemicals that can be readily ingested via dietary exposure and other exposure routes and can accumulate through the food chain. Many organic pollutants increase the risk of ovarian cancer depending on their estrogenic effects. Nonetheless, most previous studies have focused on the toxic effects of these pollutants on the proliferation, metastasis and development of ovarian cancer cells. However, little research has investigated the adverse effect of these pollutants on ovarian cancer stem cells. The current study found that BPA, PCB126 and PCB153 greatly enhanced the formation of cancer stem-like cell spheres of OVCAR-3 cells (human ovarian cancer cells) under low-dose exposure. In parallel, the CD44 high CD24 low cell subpopulation was increased in treated cells relative to untreated cells. Elevated expression of cancer stem cell markers, including ALDH1A1, CD133, SOX2, NANOG and OCT4, was demonstrated in treated cells compared to untreated cells. In summary, these data demonstrate that the oncogenic effects of pollutants can be evaluated according to changes in caner stem cell properties. Highlights: BPA, PCB126 and PCB153 enhanced the formation of stem cell sphere in OVCAR-3 cells. CD44 high CD24 low cell subpopulation was increased in tereatment treatment groups. Elevated expression of cancer stem cell markers and CD44 high CD24 low cell subpopulation indicated the increased risk of tumor growth.